Development of a methodology for the analysis of radionuclide impurities in radiopharmaceuticals by gamma-ray spectrometry - Eduardo Bonfim De Paula; Miriam Tainá Ferreira de Araújo; Roberto Poledna; José Ubiratan Delgado; Anderson Leiras (Brazilian Journal of Radiation Sciences, 2017)
LNMRI has sought to develop a methodology for the identification and accurate detection of impurities emitting gamma radiation at the metrological level, aiming to meet the recommendations not only of the international pharmacopoeia, but also of CNEN and ANVISA regarding quality control that can ensure patients That the doses received by the practices are as low as practicable. As an initial goal, it was possible to obtain an efficiency curve with uncertainty around 1% necessary to start future measurements of interest applied to nuclear medicine and to begin the development of the impurities analysis technique.